THE IMPACT OF FACILITY AND LOCATION ON THE DECISION TO STAY AT PONDOK HEXA, UJUNG GENTENG, SUKABUMI - Djohari Somad; Myrza Rahmanita (Sean Institute, 2023)
This study aims to find out the impact of Facility and Location on the Decision to Stay at Pondok Hexa, Ujung Genteng, Sukabumi. The study is a quantitative method research. The data in this study gathered using questionnaire with 100 research respondents and analyzed by SPSS 22. The sample used in this study is random sampling, where each unit of analysis has the same opportunity to become a member of the sample. Based on the results, it is known that both facility and location have a positive impact on the Decision to Stay at Pondok Hexa, Ujung Genteng, Sukabumi.